2019
DOI: 10.1108/lodj-07-2018-0245
|View full text |Cite
|
Sign up to set email alerts
|

The mediation between participative leadership and employee exploratory innovation

Abstract: Purpose The purpose of this paper is to examine the role of intermediate knowledge mechanisms on the participative leadership–employee exploratory innovation relationship using a distal mediation model. Design/methodology/approach Deploying a time-lagged questionnaire method implemented over four business quarters, data are generated from 1,600 responses in R&D units of Taiwanese technology firms. Findings The structural equation modeling results reveal that participative leadership is positively relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 95 publications
3
25
0
Order By: Relevance
“…Second, developing the social exchange perspective, participative leaders' behaviors stimulate the development of a smooth relationship with followers, which encourages employees' positive response as helping behaviors. These findings of a positive relationship between participative leadership and work-related outcomes extend the previous empirical findings (Bortoluzzi et al, 2014;Chan, 2019;Chang et al, 2019) from the leadership level to the subordinate level. Finally, the current study contributes to the effectiveness of participative leadership by empirically testing leader behavioral integrity as an imperative contingent factor for describing the relationship between participative leadership and employees' workrelated outcomes, i.e., workplace thriving and helping behaviors.…”
Section: Theoretical Implicationssupporting
confidence: 88%
See 1 more Smart Citation
“…Second, developing the social exchange perspective, participative leaders' behaviors stimulate the development of a smooth relationship with followers, which encourages employees' positive response as helping behaviors. These findings of a positive relationship between participative leadership and work-related outcomes extend the previous empirical findings (Bortoluzzi et al, 2014;Chan, 2019;Chang et al, 2019) from the leadership level to the subordinate level. Finally, the current study contributes to the effectiveness of participative leadership by empirically testing leader behavioral integrity as an imperative contingent factor for describing the relationship between participative leadership and employees' workrelated outcomes, i.e., workplace thriving and helping behaviors.…”
Section: Theoretical Implicationssupporting
confidence: 88%
“…Prior studies show that various positive leadership styles, such as servant leadership (Usman et al, 2021), empowering leadership (Li et al, 2016), ambidextrous leadership (Usman et al, 2020), authentic leadership (Mortier et al, 2016), and transformational leadership (Niessen et al, 2017), are important in fostering positive individual employee outcomes such as workplace thriving. However, although participative leadership leads to several positive outcomes (Bortoluzzi et al, 2014;Chan, 2019;Chang et al, 2019), its impact on workplace thriving is still relatively unexplored in research studies.…”
Section: Participative Leadership and Employees' Workplace Thrivingmentioning
confidence: 99%
“…Participative leadership and creative process engagement When participative leaders engage employees in decision-making and problem-solving, employees feel encouraged, supported and responsible for making creative contributions (Fatima et al, 2017). We diverge from Chang et al (2019), who used a distal mediation model to explore how participative leadership enhances exploratory innovations. Instead, we use social information processes theory as the basis for arguing that participative leadership is related to creative process engagement (i.e.…”
Section: Participative Leadership and Employee Creativitymentioning
confidence: 99%
“…Conversely, Tung and Yu (2016) used a parallel mediation model to show that participative and supportive leadership are positively associated with creativity, partially mediated by employee promotion focus. In contrast, Chang et al (2019) suggested a sequential and joint mediation effect drawing on organizational learning theory to reveal that coworker knowledge and absorptive capacities partially mediate the relationship between participative leadership and employees' exploratory innovation, both independently and jointly. Chang et al (2019) echoed prior studies of sequential mediation impacts on employee outcomes (Lythreatis et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation